Pharmacological Treatment of Body Dysmorphic Disorder - Hong, Kevin; Nezgovorova, Vera; Uzunova, Genoveva; Schlussel, Danya; Hollander, Eric (Current Neuropharmacology, 2019)
Body dysmorphic disorder is a challenging disorder that manifests as erroneously perceived flaws in one’s physical appearance and repetitive behaviors in response to appearance concerns. This disorder is also frequently comorbid with other psychiatric disorders, including major depressive disorder and autism spectrum disorder. It is currently understood to arise from a combination of biological, psychological, and environmental factors. Treatment of body dysmorphic disorder typically consists of a combination of pharmacotherapy and cognitive behavioral therapy. However, not all patients respond to treatment, and BDD symptoms remain even in those who do respond. This review outlines current pharmacological and neuromodulation treatments for body dysmorphic disorder and suggests directions for future studies of novel treatments such as augmentation with atypical antipsychotics and the use of intranasal oxytocin in cases of body dysmorphic disorder that show residual symptomatology even with tailored monotherapy. There is emerging evidence suggesting that non-invasive neurostimulatory techniques, such as repetitive transcranial magnetic stimulation, may be of value in treatment-resistant cases.
Keywords: OCRD